ECMWF TOGA Global Advanced Operational Surface Analysis, daily 1985-2010 - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 1991)
This dataset contains the high resolution output from the ECMWF operational model. This set contains only surface data on a gaussian (N80) grid with a resolution of about 1.125 degrees.